2010
DOI: 10.1021/ja105250f
|View full text |Cite
|
Sign up to set email alerts
|

Double Protonation of 1,5-Bis(triarylaminoethynyl)anthraquinone To Form a Paramagnetic Pentacyclic Dipyrylium Salt

Abstract: Protonation-induced intramolecular cyclization reactions of new donor (D)-acceptor (A) and D-A-D conjugated molecules 1-triarylaminoethynylanthraquinone (1-AmAq) and 1,5-bis(triarylaminoethynyl)anthraquinone (1,5-Am(2)Aq), respectively, were achieved. The former undergoes monoprotonation with bis(trifluoromethanesulfone)imide acid (TFSIH) to give pyrylium salt [1-AmPyl]TFSI, whereas the latter undergoes a novel double proton cyclization reaction to yield 1,5-bis(triarylamino)dipyrylium salt [1,5-Am(2)Pyl(2)](T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…3, the crystallographic analysis suggests typical propeller-like arrangements for the three aromatic rings around each nitrogen center with respect to the triarylamine termini. The bond parameters including the C—C and C—N distances and the C—N—C angles, fall in the normal range of the data reported in similar systems4344. In addition, a good coincidence between these data and the corresponding computed values can also be found in the later content.…”
Section: Resultssupporting
confidence: 77%
“…3, the crystallographic analysis suggests typical propeller-like arrangements for the three aromatic rings around each nitrogen center with respect to the triarylamine termini. The bond parameters including the C—C and C—N distances and the C—N—C angles, fall in the normal range of the data reported in similar systems4344. In addition, a good coincidence between these data and the corresponding computed values can also be found in the later content.…”
Section: Resultssupporting
confidence: 77%
“…[10] This result indicated that the majority of molecules in equilibrium between the valence tautomers, as shown in Scheme 2, were present in the diamagnetic form. Therefore, DFT calculations were performed for [1,4-Am 2 Pyl 2 ]…”
Section: Resultsmentioning
confidence: 92%
“…Heterocyclic compoundscontaining nitrogen and oxygen atoms play an important role in pharmaceutical, agrochemical, and materials chemistry . Recent years, by utilizing varieties of heterocyclic moieties, a large number of drugs and agrochemical products were reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect is that the lipophilic nature of the chromene derivatives helps to peeve the cell membrane effectively . Additionally, benzopyran derivatives also played imperative performance in organic material chemistry like fluorescent dyes, pigments, synthetic fibers, molecular devices , and electrophotographic.…”
Section: Introductionmentioning
confidence: 99%